The use of concurrent long-acting injectable antipsychotic therapy with paliperidone palmitate and aripiprazole monohydrate in a patient with schizophrenia - Christopher Evernden, BSc, BScPharm, ACPR; Irene Giang, BScPharm; Mariah Anderson, BScPharm (American Association of Psychiatric Pharmacists, 2021)
International schizophrenia guidelines endorse seeking the patient's preference for guiding antipsychotic therapy. There exists a small niche of patients who prefer, or are required to use, long-acting injectable antipsychotic medications due to the adherence benefit. However, they may not be able to achieve adequate symptom reduction prior to experiencing treatment-limiting adverse effects from a single agent. Here, we present a patient case prescribed concurrent long-acting injectable antipsychotic therapy with paliperidone palmitate and aripiprazole monohydrate due to patient preference in the setting of a history of nonadherence to oral medications, treatment-limiting adverse effects to long-acting injectable paliperidone, and failure to achieve adequate symptom reduction with long-acting injectable aripiprazole monotherapy.